In vitro Activity of Contezolid Against Methicillin-Resistant Staphylococcus aureus, Vancomycin-Resistant Enterococcus, and Strains With Linezolid Resistance Genes From China - Wang, Siheng; Cai, Chang; Shen, Yingbo; Sun, Chengtao; Shi, Qingxin; Wu, Ningjun; Zheng, Shufang; Qian, Jiao; Zhang, Rong; Zhou, Hongwei (Frontiers in Microbiology, 2021)
Contezolid is a novel oxazolidinone, which exhibits potent activity against gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and penicillin-resistant Streptococcus pneumoniae (PRSP). In this study, the in vitro activity of contezolid was compared with linezolid (LZD), tigecycline (TGC), teicoplanin (TEC), vancomycin (VA), daptomycin (DAP), and florfenicol (FFC) against MRSA and VRE strains isolated from China. Contezolid revealed considerable activity against MRSA and VRE isolates with MIC90 values of 0.5 and 1.0μg/mL, respectively. For VRE strains with different resistance genotypes, including vanA- and vanM-type strains, contezolid did not exhibit significantly differential antibacterial activity. Furthermore, the antimicrobial activity of contezolid is similar to or slightly better than that of linezolid against MRSA and VRE strains. Subsequently, the activity of contezolid was tested against strains carrying linezolid resistance genes, including Staphylococcus capitis carrying cfr gene and Enterococcus faecalis carrying optrA gene. The results showed that contezolid exhibited similar antimicrobial efficacy to linezolid against strains with linezolid resistance genes. In general, contezolid may have potential benefits to treat the infections caused by MRSA and VRE pathogens.